Assessment of cardiac sympathetic activity by MIBG imaging in patients with heart failure: a clinical appraisal. Issue 22 (13th September 2011) - Perrone-Filardi, Pasquale; Paolillo, Stefania; Dellegrottaglie, Santo; Gargiulo, Paola; Savarese, Gianluigi; Marciano, Caterina; Casaretti, Laura; Cecere, Milena; Musella, Francesca; Pirozzi, Elisabetta; Parente, Antonio; Cuocolo, Alberto
Abstract : Cardiac sympathetic activity can be assessed by 123 I-labelled meta-iodobenzylguanidine (MIBG) scintigraphy. Abnormalities of sympathetic cardiac activity have been shown in patients with heart failure, resulting in reduced MIBG uptake. Abnormal MIBG uptake predicts cardiac death, arrhythmias and all-cause mortality in patients with heart failure with a prognostic power incremental to that of conventional risk markers, and may identify patients at low risk of arrhythmias despite current guideline indications for implantable cardioverter defibrillator or patients at high risk for arrhythmias not fulfilling implantable cardioverter defibrillator indications. Prospective outcome studies are needed to assess whether MIBG imaging will have an impact on the mortality and morbidity of patients with heart failure.